2003
DOI: 10.1097/00004703-200308000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Malingering by Proxy: A Form of Pediatric Condition Falsification

Abstract: The deliberate production or feigning of signs or symptoms in a child by a caretaker is well recognized as factitious disorder by proxy, a psychiatric condition commonly reported in the pediatric literature. However, it is not as well recognized that the false illness portrayal may also be the result of a parent instructing the child to malinger. A case report of a 13-year-old patient who feigned an immobile upper extremity for the purpose of obtaining a legal settlement is presented. Physicians are encouraged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…We agree with Stutts et al's proposal of a team‐based approach in the ongoing follow‐up of the child, including possible involvement from psychiatric and psychological care, and social and child protective services. In cases of malingering by child proxy, prudent physicians would benefit from obtaining collateral information about the child's condition from other professionals involved in the child's care.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We agree with Stutts et al's proposal of a team‐based approach in the ongoing follow‐up of the child, including possible involvement from psychiatric and psychological care, and social and child protective services. In cases of malingering by child proxy, prudent physicians would benefit from obtaining collateral information about the child's condition from other professionals involved in the child's care.…”
Section: Discussionsupporting
confidence: 86%
“…Stutts et al reported a case in which a 13‐year‐old boy presented with his parents to numerous physicians with a history of right upper limb pain, weakness, decreased range of motion, and tingling, presumably related to a traumatic injury at school. Multiple investigations including neurological testing and imaging were normal.…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36][37] Outright malingering is apt to occur less frequently in children, although multiple case reports and case series have documented that children provide noncredible responses at least occasionally during health care examinations. [38][39][40][41][42][43][44][45][46][47][48][49][50] Only 1 identified study has focused on how frequently noncredible responding occurs after pediatric mTBI specifically. A consecutive neuropsychological case series of ours consisting of 193 school-aged children found that 17% of the sample failed a performance validity test (PVT).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the primary threat to valid measurement was the possibility of an effort on the part of the parent or child to present him or herself in an excessively negative light. As noted previously, children have been known to malinger [30,31]. Moreover, due to the impressionable state of most children, it is relatively easy for a parent to either intentionally or unintentionally promote the expression of symptoms in children [51].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinicians believe that children, particularly younger ones, lack the ability to intentionally misrepresent their symptoms. There is evidence, however, of malingering by children who may be influenced by powerful others (e.g., parents) who stood to gain substantially if the child appeared impaired [30,31]. Of course the literature on symptom exaggeration and malingering in adults is extensive and beyond the scope of this paper.…”
Section: Effects Of a Community Toxic Release On The Psychological Stmentioning
confidence: 91%